Investigation of optimal parameters for chest radiograph imaging using film-screen and computed radiography - Sun, Zhonghua; Siddiqu, Salim; Ng, K.; Ramli, K.; Davidson, R. (Chinese Society of Medical Physics, 2007)
Objective: Digital imaging is gradually replacing the conventional film-screen (FS) imaging technology. This is mainly due to the perceived advantages of digital image processing, electronic archiving, teleradiology and the potential for optimisation of image acquisition and display independently. Chest radiography is the commonest examination performed in most radiology departments worldwide. In digital chest radiography, examination parameters such as tube voltage and tube current have been frequently adopted from FS technology. However, exposures optimised for FS systems are not necessarily optimal for digital systems. The aim of the study was to determine the optimal tube potential for chest imaging using computed radiography (CR), and to assess the comparative image quality of FS and CR as a function of tube voltage, based on a phantom study.Materials and Methods: A chest phantom was constructed to perform the experiments. The phantom was made from sheets of plastic tubing, copper and aluminium, which were shaped to resemble frontal radiographic projections of human thoracic structures. The lungs, heart, ribs and abdomen were oriented and arranged to simulate a projection of a thorax and sandwiched between Perspex to provide X-ray attenuation and scatter properties similar to those of a human chest at diagnostic X-ray energies. Regional test objects were incorporated into the chest phantom for image quality assessment in the lungs, heart and retrodiaphragmatic areas. Each test object contained a matrix of low-contrast objects for contrast detail assessment. A line-pair phantom was included in the lung-equivalent, heart-equivalent and subdiaphragm-equivalent regions for the assessment of spatial resolution.Chest phantom images were taken using both FS and CR on an Agfa system. Imaging parameters were selected with variable mAs ranging from 0.5 to 8, and tube voltage ranging from 80 to 120 kv. Quantitative measurements of image quality were performed at 8 regions of interest to determine the relationship between image noise and imaging parameters. Subjective assessment was conducted to visualise the demonstration of anatomic structures and the contrast detail.Results: Our results showed that for FS chest imaging, a protocol of 90 kv and 2 mAs resulted in the lowest image noise with acceptable image quality compared to other protocols (p<0.001), while for CR chest imaging, a protocol of 120 kv and 2 mAs resulted in the lowest image noise with acceptable image quality compared to other protocols (p<0.001). With CR chest imaging, a protocol of 120 kv and 2 mAs was further confirmed to be optimal by comparing with variable mAs values (0.5 to 8 mAs) through correlating quantitative measurements with subjective assessment.Conclusion: Our study demonstrated that CR and FS have inherently different imaging characteristics. It is therefore necessary to optimise the exposure factors when changing from FS to CR systems. For chest imaging the results reported here indicate that CR produces optimum image quality in the protocol of 120 kv and 2 mAs, higher than the relative lower energy noticed in FS which is 90 kv and 2 mAs. Clinical trials are required to verify the results.